Differentiation and Diversification in Emerging African Higher Education - Langa, Patrico (International Higher Education, 2023)
This article examines the differentiation and diversification processes in African higher education and their implications for further research and policy. These processes are perhaps among the most well-established concepts to help understand social and organizational change in African higher education systems and institutions. Founded in social theory, they shed light onto mostly tacit, rather than institutional, social and policy practices by different African higher education stakeholders, while guiding change toward increased democratic governance.